Delayed [18F]-FDG PET Imaging Increases Diagnostic Performance and Reproducibility to Differentiate Recurrence of Brain Metastases From Radionecrosis. (11th September 2022) - Otman, Hosameldin; Farce, Julien; Meneret, Pierre; Palard-Novello, Xavier; Le Reste, Pierre-Jean; Lecouillard, Isabelle; Vauleon, Elodie; Chanchou, Marion; Carsin Nicol, Beatrice; Bertaux, Marc; Devillers, Anne; Mariano-Goulart, Denis; et al.
Abstract : Purpose: Differentiating brain metastasis recurrence from radiation necrosis can be challenging during MRI follow-up after stereotactic radiotherapy. [ 18 F]-FDG is the most available PET tracer, but standard images performed 30 to 60 minutes postinjection provide insufficient accuracy. We compared the diagnostic performance and interobserver agreement of [ 18 F]-FDG PET with delayed images (4–5 hours postinjection) with the ones provided by standard and dual-time-point imaging. Methods: Consecutive patients referred for brain [ 18 F]-FDG PET after inconclusive MRI were retrospectively included between 2015 and 2020 in 3 centers. Two independent nuclear medicine physicians interpreted standard (visually), delayed (visually), and dual-time-point (semiquantitatively) images, respectively. Adjudication was applied in case of discrepancy. The final diagnosis was confirmed histologically or after 6 months of MRI follow-up. Areas under the receiver operating characteristic curves were pairwise compared. Results: Forty-eight lesions from 46 patients were analyzed. Primary tumors were mostly located in the lungs (57%) and breast (23%). The median delay between radiotherapy and PET was 15.7 months. The final diagnosis was tumor recurrence in 24 of 48 lesions (50%), with histological confirmation in 19 of 48 lesions (40%). Delayed images provided a larger area under the receiver operating characteristic curve (0.88; 95% confidence interval [CI], 0.75–0.95) than both standard (0.69; 95% CI, 0.54–0.81; P = 0.0014) and dual-time-point imaging (0.77; 95% CI, 0.63–0.88; P = 0.045), respectively. Interobserver agreement was almost perfect with delayed images ( κ = 0.83), whereas it was moderate with both standard ( κ = 0.48) and dual-time-point images ( κ = 0.61). Conclusions: [ 18 F]-FDG PET with delayed images is an accurate and reliable alternative to differentiate metastasis recurrence from radiation necrosis in case of inconclusive MRI after brain stereotactic radiotherapy.